A Live Attenuated H9N2 Influenza Vaccine Is Well Tolerated and Immunogenic in Healthy Adults - Karron, Ruth A. (2009)
Development of live attenuated influenza vaccines (LAIV) against avian strains with pandemic potential is an important public-health strategy. Either 1 or 2 10(7)-TCID(50) doses of H9N2 LAIV A/chicken/Hong Kong/G9/97 were administered intranasally to 50 adults in isolation; 41 participants were H9N2 seronegative, 24 of whom received 2 doses. The vaccine was well tolerated; vaccine shedding was minimal. After 2 doses, 92% of H9-seronegative participants had ≥4-fold increases in hemagglutination-inhibition antibody, and 79% had ≥4-fold increases in neutralizing antibody; 100% had responses detected by at least 1 assay. Although replication of the H9N2 LAIV was restricted, 2 doses were immunogenic in H9N2-seronegative adults.